The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1021/acsnano.3c09852
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the Boundaries of Immunotherapy in Lung Adenocarcinoma with Idiopathic Pulmonary Fibrosis by a Biomimetic Proteinoid Enabling Selective Endocytosis

Aimin Jiang,
Xiaoqiang Zheng,
Siqi Yan
et al.

Abstract: The coexistence of lung adenocarcinoma (LUAD) with idiopathic pulmonary fibrosis (IPF), which has been extensively documented as a prominent risk factor for checkpoint inhibitor-related pneumonitis (CIP) in patients undergoing immunotherapy, has long been considered a restricted domain for the use of immune checkpoint inhibitors (ICIs). To overcome it, an approach was employed herein to specifically target PD-L1 within the cellular interior, surpassing the conventional focus solely on the cytomembrane, thereby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…They concluded CM-NPs hold great potential as a pivotal drug delivery strategy in the diagnosis and treatment of various malignancies, including breast cancer. Recent studies have revealed that biomimetic nanoparticles derived from erythrocyte membranes exhibit excellent tumor-targeting capabilities by altering the endocytosis mechanism (6,21). A recent study has introduced an innovative approach by developing an erythrocyte membrane biomimetic ICI proteinoid to selectively inhibit tumor cell PD-L1 via a distinct endocytosis pathway between cancerous and non-cancerous cells (6).…”
Section: Zhou Et Al Reviewed Recent Advances In the Use Of Cancer Cel...mentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded CM-NPs hold great potential as a pivotal drug delivery strategy in the diagnosis and treatment of various malignancies, including breast cancer. Recent studies have revealed that biomimetic nanoparticles derived from erythrocyte membranes exhibit excellent tumor-targeting capabilities by altering the endocytosis mechanism (6,21). A recent study has introduced an innovative approach by developing an erythrocyte membrane biomimetic ICI proteinoid to selectively inhibit tumor cell PD-L1 via a distinct endocytosis pathway between cancerous and non-cancerous cells (6).…”
Section: Zhou Et Al Reviewed Recent Advances In the Use Of Cancer Cel...mentioning
confidence: 99%
“…In vivo experiments have shown that the biomimetic ICI proteinoid not only reactivates the anti-tumor immune response in a murine model of lung adenocarcinoma with coexisting idiopathic pulmonary fibrosis but also demonstrates a favorable safety profile by effectively eliminating any irAEs. This breakthrough broadens the boundaries of immunotherapy in lung cancer treatment (6).…”
Section: Zhou Et Al Reviewed Recent Advances In the Use Of Cancer Cel...mentioning
confidence: 99%